Difference between revisions of "2021 AMC 12A Problems/Problem 22"

m (Solution)
m (Remark)
 
(72 intermediate revisions by 7 users not shown)
Line 2: Line 2:
 
Suppose that the roots of the polynomial <math>P(x)=x^3+ax^2+bx+c</math> are <math>\cos \frac{2\pi}7,\cos \frac{4\pi}7,</math> and <math>\cos \frac{6\pi}7</math>, where angles are in radians. What is <math>abc</math>?
 
Suppose that the roots of the polynomial <math>P(x)=x^3+ax^2+bx+c</math> are <math>\cos \frac{2\pi}7,\cos \frac{4\pi}7,</math> and <math>\cos \frac{6\pi}7</math>, where angles are in radians. What is <math>abc</math>?
  
<math>\textbf{(A) }-\frac{3}{49} \qquad \textbf{(B) }-\frac{1}{28} \qquad \textbf{(C) }\frac{^3\sqrt7}{64} \qquad \textbf{(D) }\frac{1}{32}\qquad \textbf{(E) }\frac{1}{28}</math>
+
<math>\textbf{(A) }-\frac{3}{49} \qquad \textbf{(B) }-\frac{1}{28} \qquad \textbf{(C) }\frac{\sqrt[3]7}{64} \qquad \textbf{(D) }\frac{1}{32}\qquad \textbf{(E) }\frac{1}{28}</math>
  
==Solution==
+
==Solution 1==
  
Part 1: solving for c  
+
Part 1: solving for a
 +
 
 +
<math>a</math> is the negation of the sum of roots
 +
 
 +
<math>a = - \left( \cos \frac{2\pi}7 + \cos \frac{4\pi}7 + \cos \frac{6\pi}7 \right)</math>
 +
 
 +
The real values of the 7th roots of unity are: <math>1, \cos \frac{2\pi}7, \cos \frac{4\pi}7, \cos \frac{6\pi}7, \cos \frac{8\pi}7, \cos \frac{10\pi}7, \cos \frac{12\pi}7</math> and they sum to <math>0</math>.
 +
 
 +
If we subtract 1, and condense identical terms, we get:
 +
 
 +
<math>2\cos \frac{2\pi}7 + 2\cos \frac{4\pi}7 + 2\cos \frac{6\pi}7 = -1</math>
 +
 
 +
Therefore, we have <math>a = -\left(-\frac{1}2\right) = \frac{1}2</math>
 +
 
 +
 
 +
Part 2: solving for b
 +
 
 +
<math>b</math> is the sum of roots two at a time by Vieta's
 +
 
 +
<math>b = \cos \frac{2\pi}7 \cos \frac{4\pi}7 + \cos \frac{2\pi}7 \cos \frac{6\pi}7 + \cos \frac{4\pi}7 \cos \frac{6\pi}7</math>
 +
 
 +
We know that <math>\cos \alpha \cos \beta = \frac{ \cos \left(\alpha + \beta\right) + \cos \left(\alpha - \beta\right) }{2}</math>
 +
 
 +
By plugging all the parts in we get:
 +
 
 +
<math> \frac{\cos \frac{6\pi}7 + \cos \frac{2\pi}7}2 + \frac{\cos \frac{4\pi}7 + \cos \frac{4\pi}7}2 + \frac{\cos \frac{6\pi}7 + \cos \frac{2\pi}7}2 </math>
 +
 
 +
Which ends up being:
 +
 
 +
<math> \cos \frac{2\pi}7 + \cos \frac{4\pi}7 + \cos \frac{6\pi}7 </math>
 +
 
 +
Which was shown in the first part to equal <math>-\frac{1}2</math>, so <math>b = -\frac{1}2</math>
 +
 
 +
 
 +
 
 +
Part 3: solving for c
  
 
Notice that <math>\cos \frac{6\pi}7 = \cos \frac{8\pi}7</math>
 
Notice that <math>\cos \frac{6\pi}7 = \cos \frac{8\pi}7</math>
Line 14: Line 49:
 
<math>c = -\cos \frac{2\pi}7 \cos \frac{4\pi}7 \cos \frac{8\pi}7</math>
 
<math>c = -\cos \frac{2\pi}7 \cos \frac{4\pi}7 \cos \frac{8\pi}7</math>
  
Multiply by <math>8 \frac{\sin{2\pi}}{7}</math>
+
Multiply by <math>8 \sin{\frac{2\pi}{7}}</math>
  
<math>c 8 \sin{2\pi}7 = -8 \frac{\sin{2\pi}}{7} \cos \frac{2\pi}7 \cos \frac{4\pi}7 \cos \frac{8\pi}7</math>
+
<math>c \cdot 8 \sin{\frac{2\pi}{7}} = -8 \sin{\frac{2\pi}{7}} \cos \frac{2\pi}7 \cos \frac{4\pi}7 \cos \frac{8\pi}7</math>
  
 
Then use sine addition formula backwards:
 
Then use sine addition formula backwards:
Line 22: Line 57:
 
<math>2 \sin \frac{2\pi}7 \cos \frac{2\pi}7 = \sin \frac{4\pi}7</math>
 
<math>2 \sin \frac{2\pi}7 \cos \frac{2\pi}7 = \sin \frac{4\pi}7</math>
  
<math>c 8 \sin{2\pi}7 = -4 \sin \frac{4\pi}7 \cos \frac{4\pi}7 \cos \frac{8\pi}7</math>
+
<math>c \cdot 8 \sin{\frac{2\pi}{7}} = -4 \sin \frac{4\pi}7 \cos \frac{4\pi}7 \cos \frac{8\pi}7</math>
  
<math>c 8 \sin{2\pi}7 = -2 \sin \frac{8\pi}7 \cos \frac{8\pi}7</math>
+
<math>c \cdot 8 \sin{\frac{2\pi}{7}} = -2 \sin \frac{8\pi}7 \cos \frac{8\pi}7</math>
  
<math>c 8 \sin{2\pi}7 = -\sin \frac{16\pi}7</math>
+
<math>c \cdot 8 \sin{\frac{2\pi}{7}} = -\sin \frac{16\pi}7</math>
  
<math>c 8 \sin{2\pi}7 = -\sin \frac{2\pi}7</math>
+
<math>c \cdot 8 \sin{\frac{2\pi}{7}} = -\sin \frac{2\pi}7</math>
  
 
<math>c = -\frac{1}8</math>
 
<math>c = -\frac{1}8</math>
  
  
Part 2: starting to solve for b
 
  
<math>b</math> is the sum of roots two at a time by Vieta's
+
Finally multiply <math>abc = \frac{1}2 * - \frac{1}2 * -\frac{1}8 = \frac{1}{32}</math> or <math>\boxed{D) \frac{1}{32}}</math>.
 +
 
 +
~Tucker
 +
 
 +
== Solution 2 (Approximation) ==
 +
Letting the roots be <math>p</math>, <math>q</math>, and <math>r</math>, Vietas gives
 +
<cmath>p + q + r = a</cmath>
 +
<cmath>pq + qr + pq = -b</cmath>
 +
<cmath>pqr = c</cmath>
 +
We use the Taylor series for <math>\cos x</math>,
 +
<cmath>\cos x = \sum_{k = 0}^{\infty} (-1)^k \frac{x^{2k}}{(2k)!}</cmath>
 +
to approximate the roots. Taking the sum up to <math>k = 3</math> yields a close approximation, so we have
 +
<cmath>\cos\left(\frac{2\pi}{7}\right) \simeq 1-\frac{\left(\frac{2\pi}{7}\right)^{2}}{2}+\frac{\left(\frac{2\pi}{7}\right)^{4}}{24}-\frac{\left(\frac{2\pi}{7}\right)^{6}}{720} \simeq 0.623</cmath>
 +
<cmath>\cos\left(\frac{4\pi}{7}\right) \simeq 1-\frac{\left(\frac{4\pi}{7}\right)^{2}}{2}+\frac{\left(\frac{4\pi}{7}\right)^{4}}{24}-\frac{\left(\frac{4\pi}{7}\right)^{6}}{720} \simeq -0.225</cmath>
 +
<cmath>\cos\left(\frac{6\pi}{7}\right) \simeq 1-\frac{\left(\frac{6\pi}{7}\right)^{2}}{2}+\frac{\left(\frac{6\pi}{7}\right)^{4}}{24}-\frac{\left(\frac{6\pi}{7}\right)^{6}}{720} \simeq -0.964.</cmath>
 +
Note that these approximations get worse as <math>x</math> gets larger, but they will be fine for the purposes of this problem. We then have
 +
<cmath>p + q + r = a \simeq -0.56</cmath>
 +
<cmath>pq + qr + pr = -b \simeq -0.524</cmath>
 +
<cmath>pqr = c \simeq 0.135</cmath>
 +
We further approximate these values to <math>a \simeq -0.5</math>, <math>b \simeq 0.5</math>, and <math>c \simeq 0.125</math> (mostly as this is an AMC problem and will likely use nice fractions). Thus, we have <math>abc \simeq \boxed{\textbf{(D) } \frac{1}{32}}</math>. ~ciceronii
 +
 
 +
Remark: In order to be more confident in your answer, you can go a few terms further in the Taylor series.
 +
 
 +
== Solution 3 (Only Using Product to Sum Identity) ==
 +
Note sum of roots of unity equal zero, sum of real parts equal zero, and <math>\text{Re} \omega^{m} = \text{Re} \omega^{-m},</math>
 +
thus <math>\cos \frac{2 \pi}{7} + \cos \frac{4 \pi}{7} + \cos \frac{6 \pi}{7} = 1/2(0 - \cos 0) = -1/2</math> which means <math>A = \frac{1}{2}.</math>
 +
 
 +
By product to sum, <math>\cos \frac{2 \pi}{7} \cos \frac{4 \pi}{7} + \cos \frac{2 \pi}{7} \cos \frac{6 \pi}{7} + \cos \frac{4 \pi}{7} \cos \frac{6 \pi}{7} = \frac{1}{2} (2 \cos \frac{2 \pi}{7} + \cos \frac{4 \pi}{7} + \cos \frac{6 \pi}{7} + \cos \frac{8 \pi}{7} + \cos \frac{10 \pi}{7}) </math>
 +
<math>= \frac{1}{2}(2 \cos \frac{2 \pi}{7} + 2 \cos \frac{4 \pi}{7} + 2 \cos \frac{6 \pi}{7}) = -1/2,</math> so <math>B = - \frac{1}{2}.</math>
 +
 
 +
By product to sum, <math>\cos \frac{2 \pi}{7} \cos \frac{4 \pi}{7} \cos \frac{6 \pi}{7} = \frac{1}{2}(\cos \frac{2 \pi}{7} + \cos \frac{6 \pi}{7}) \cos \frac{6 \pi}{7} = \frac{1}{4}(\cos \frac{4 \pi}{7} +  \cos \frac{8 \pi}{7}) + \frac{1}{4}(1 + \cos \frac{12 \pi}{7})</math>
 +
<math>= \frac{1}{4}(1 + \cos\frac{2\pi}{7} + \cos \frac{4\pi}{7} + \cos \frac{6\pi}{7}) = 1/8,</math> so <math>C = -1/8.</math>
 +
 
 +
<math>ABC =\boxed{ \frac{1}{32}}.</math>
  
<math>b = \cos \frac{2\pi}7 \cos \frac{4\pi}7 + \cos \frac{2\pi}7 \cos \frac{6\pi}7 + \cos \frac{4\pi}7 \cos \frac{6\pi}7</math>
+
~ ccx09
  
We know that <math>\cos \alpha \cos \beta = /frac{ \cos \left(\alpha + \beta\right) + \cos \left(\alpha - \beta\right) }2</math>
+
==Solution 4 (Complex Numbers)==
 +
Using geometric series, we can show that <math>\sum_{k=0}^{6}e^{\frac{2k\pi i}{7}}=0:</math> <cmath>\sum_{k=0}^{6}e^{\frac{2k\pi i}{7}}=1+e^{\frac{2\pi i}{7}}+e^{\frac{4\pi i}{7}}+\cdots+e^{\frac{12\pi i}{7}}=\frac{1-1}{1-e^{\frac{2\pi i}{7}}}=0.</cmath>
  
By plugging all the parts in we get:
+
Alternatively, note that the <math>7</math>th roots of unity are <math>z=e^{\frac{2k\pi i}{7}}</math> for <math>i=0,1,2,\cdots,6,</math> in which <math>z^7-1=0.</math> By Vieta's Formulas, the sum of these seven roots is <math>0.</math>
  
<math> \frac{\cos \frac{6\pi}7 + \cos \frac{2\pi}7}2 + \frac{\cos \frac{4\pi}7 + \cos \frac{4\pi}7}2 + \frac{\cos \frac{6\pi}7 + \cos \frac{2\pi}7}2 </math>
+
It follows that the real parts of these complex numbers must sum to <math>0,</math> so we get
 +
<cmath>\begin{align*}
 +
\sum_{k=0}^{6}\cos\frac{2k\pi}{7}&=0 \\
 +
\sum_{k=1}^{6}\cos\frac{2k\pi}{7}&=-1.
 +
\end{align*}</cmath>
 +
Since <math>\cos\theta=\cos(2\pi-\theta)</math> holds for all <math>\theta,</math> we can rewrite this as
 +
<cmath>\begin{align*}
 +
\cos\frac{2\pi}{7}+\cos\frac{4\pi}{7}+\cos\frac{6\pi}{7}+\underbrace{\cos\frac{8\pi}{7}}_{\cos\tfrac{6\pi}{7}}+\underbrace{\cos\frac{10\pi}{7}}_{\cos\tfrac{4\pi}{7}}+\underbrace{\cos\frac{12\pi}{7}}_{\cos\tfrac{2\pi}{7}}&=-1\\
 +
2\left(\cos\frac{2\pi}{7}+\cos\frac{4\pi}{7}+\cos\frac{6\pi}{7}\right)&=-1\\
 +
\cos\frac{2\pi}{7}+\cos\frac{4\pi}{7}+\cos\frac{6\pi}{7}&=-\frac12.
 +
\end{align*}</cmath>
  
Which ends up being:
+
Two solutions follow from here:
  
<math> \cos \frac{2\pi}7 + \cos \frac{4\pi}7 + \cos \frac{6\pi}7 </math>
+
===Solution 4.1 (Trigonometric Identities)===
 +
We know that <math>\theta=\frac{2\pi}{7},\frac{4\pi}{7},\frac{6\pi}{7}</math> are roots of <cmath>\cos\theta+\cos(2\theta)+\cos(3\theta)=-\frac12, \ \ \ \ \ (*)</cmath> as they can be verified algebraically (by the identity <math>\cos\theta=\cos(-\theta)=\cos(2\pi-\theta)</math> for all <math>\theta</math>) or geometrically (by the <b>Remark</b> section).
  
Which is shown in the next part to equal <math>-\frac{1}2</math>, so <math>b = -\frac{1}2</math>
+
Let <math>x=\cos\theta.</math> It follows that
 +
<cmath>\begin{align*}
 +
\cos(2\theta)&=2\cos^2\theta-1 \\
 +
&=2x^2-1, \\
 +
\cos(3\theta)&=\cos(2\theta+\theta) \\
 +
&=\cos(2\theta)\cos\theta-\sin(2\theta)\sin\theta \\
 +
&=\cos(2\theta)\cos\theta-2\sin^2\theta\cos\theta \\
 +
&=\cos(2\theta)\cos\theta-2\left(1-\cos^2\theta\right)\cos\theta \\
 +
&=\left(2x^2-1\right)x-2\left(1-x^2\right)x \\
 +
&=2x^3-x-2x+2x^3 \\
 +
&=4x^3-3x.
 +
\end{align*}</cmath>
 +
Rewriting <math>(*)</math> in terms of <math>x,</math> we have
 +
<cmath>\begin{align*}
 +
x+\left(2x^2-1\right)+\left(4x^3-3x\right)&=-\frac12 \\
 +
4x^3+2x^2-2x-\frac12&=0 \\
 +
x^3+\frac12 x^2 - \frac12 x - \frac18 &= 0,
 +
\end{align*}</cmath>
 +
in which the roots are <math>x=\cos\frac{2\pi}{7},\cos\frac{4\pi}{7},\cos\frac{6\pi}{7}.</math>
  
 +
Therefore, we obtain <math>(a,b,c)=\left(\frac12,-\frac12,-\frac18\right),</math> from which <math>abc=\boxed{\textbf{(D) }\frac{1}{32}}.</math>
  
Part 3: solving for a and b as the sum of roots
+
~MRENTHUSIASM (inspired by Peeyush Pandaya et al)
  
<math>a</math> is the negation of the sum of roots
+
===Solution 4.2 (Vieta's Formulas)===
 +
Let <math>z=e^{\frac{2\pi i}{7}}.</math> Since <math>z</math> is a <math>7</math>th root of unity, <math>z^7=1.</math> Geometrically (shown in the <b>Remark</b> section), it follows that
 +
<cmath>\begin{alignat*}{4}
 +
\cos{\frac{2\pi}{7}} &= \frac{z+z^6}{2} &&= \frac{z+z^{-1}}{2}, \\
 +
\cos{\frac{4\pi}{7}} &= \frac{z^2+z^5}{2} &&= \frac{z^2+z^{-2}}{2}, \\
 +
\cos{\frac{6\pi}{7}} &= \frac{z^3+z^4}{2} &&= \frac{z^3+z^{-3}}{2}.
 +
\end{alignat*}</cmath>
 +
Recall that <math>\sum_{k=0}^{6}z^k=0</math> (from which <math>\sum_{k=1}^{6}z^k=-1</math>), and let <math>(r,s,t)=\left(\cos{\frac{2\pi}{7}},\cos{\frac{4\pi}{7}},\cos{\frac{6\pi}{7}}\right).</math> By Vieta's Formulas, the answer is
 +
<cmath>\begin{align*}
 +
abc&=[-(r+s+t)](rs+st+tr)(-rst) \\
 +
&=(r+s+t)(rs+st+tr)(rst) \\
 +
&=\left(\frac{\sum_{k=1}^{6}z^k}{2}\right)\left(\frac{2\sum_{k=1}^{6}z^k}{4}\right)\left(\frac{1+\sum_{k=0}^{6}z^k}{8}\right) \\
 +
&=\frac{1}{32}\left(\sum_{k=1}^{6}z^k\right)\left(\sum_{k=1}^{6}z^k\right)\left(1+\sum_{k=0}^{6}z^k\right) \\
 +
&=\frac{1}{32}(-1)(-1)(1) \\
 +
&=\boxed{\textbf{(D) }\frac{1}{32}}.
 +
\end{align*}</cmath>
  
<math>a = -\cos \frac{2\pi}7 + \cos \frac{4\pi}7 + \cos \frac{6\pi}7</math>
+
~MRENTHUSIASM (inspired by Peeyush Pandaya et al)
  
The real values of the 7th roots of unity are: <math>1, \cos \frac{2\pi}7, \cos \frac{4\pi}7, \cos \frac{6\pi}7, \cos \frac{8\pi}7, \cos \frac{10\pi}7, \cos \frac{12\pi}7</math> and they sum to <math>0</math>.
+
===Remark (Geometric Representations)===
 +
Graph of the <math>7</math>th roots of unity in Desmos:
  
If we subtract 1, and condense identical terms, we get:
+
* Rectangular Coordinate System: https://www.desmos.com/calculator/rzzk5geric (shown below)
  
<math>2\cos \frac{2\pi}7 + 2\cos \frac{4\pi}7 + 2\cos \frac{6\pi}7 = -1</math>
+
* Polar Coordinate System: https://www.desmos.com/calculator/xta6sfbnot
  
Therefore, we have <math>a = -\left(-\frac{1}2\right) = \frac{1}2</math>
+
[[File:2021 AMC 12A Problem 22 Exact Values + LaTeX.png|center]]
  
Finally multiply <math>abc = \frac{1}2 * - \frac{1}2 * -\frac{1}8 = \frac{1}{32}</math> or <math>\boxed{D) \frac{1}{32}}</math>.
+
Geometrically, it is clear that the imaginary parts of these complex numbers sum to <math>0.</math>  
  
~Tucker
+
~MRENTHUSIASM
  
 
== Video Solution by OmegaLearn (Euler's Identity + Vieta's ) ==
 
== Video Solution by OmegaLearn (Euler's Identity + Vieta's ) ==
Line 77: Line 191:
 
==See also==
 
==See also==
 
{{AMC12 box|year=2021|ab=A|num-b=21|num-a=23}}
 
{{AMC12 box|year=2021|ab=A|num-b=21|num-a=23}}
 +
[[Category:Intermediate Algebra Problems]]
 
{{MAA Notice}}
 
{{MAA Notice}}

Latest revision as of 01:42, 26 June 2021

Problem

Suppose that the roots of the polynomial $P(x)=x^3+ax^2+bx+c$ are $\cos \frac{2\pi}7,\cos \frac{4\pi}7,$ and $\cos \frac{6\pi}7$, where angles are in radians. What is $abc$?

$\textbf{(A) }-\frac{3}{49} \qquad \textbf{(B) }-\frac{1}{28} \qquad \textbf{(C) }\frac{\sqrt[3]7}{64} \qquad \textbf{(D) }\frac{1}{32}\qquad \textbf{(E) }\frac{1}{28}$

Solution 1

Part 1: solving for a

$a$ is the negation of the sum of roots

$a = - \left( \cos \frac{2\pi}7 + \cos \frac{4\pi}7 + \cos \frac{6\pi}7 \right)$

The real values of the 7th roots of unity are: $1, \cos \frac{2\pi}7, \cos \frac{4\pi}7, \cos \frac{6\pi}7, \cos \frac{8\pi}7, \cos \frac{10\pi}7, \cos \frac{12\pi}7$ and they sum to $0$.

If we subtract 1, and condense identical terms, we get:

$2\cos \frac{2\pi}7 + 2\cos \frac{4\pi}7 + 2\cos \frac{6\pi}7 = -1$

Therefore, we have $a = -\left(-\frac{1}2\right) = \frac{1}2$


Part 2: solving for b

$b$ is the sum of roots two at a time by Vieta's

$b = \cos \frac{2\pi}7 \cos \frac{4\pi}7 + \cos \frac{2\pi}7 \cos \frac{6\pi}7 + \cos \frac{4\pi}7 \cos \frac{6\pi}7$

We know that $\cos \alpha \cos \beta = \frac{ \cos \left(\alpha + \beta\right) + \cos \left(\alpha - \beta\right) }{2}$

By plugging all the parts in we get:

$\frac{\cos \frac{6\pi}7 + \cos \frac{2\pi}7}2 + \frac{\cos \frac{4\pi}7 + \cos \frac{4\pi}7}2 + \frac{\cos \frac{6\pi}7 + \cos \frac{2\pi}7}2$

Which ends up being:

$\cos \frac{2\pi}7 + \cos \frac{4\pi}7 + \cos \frac{6\pi}7$

Which was shown in the first part to equal $-\frac{1}2$, so $b = -\frac{1}2$


Part 3: solving for c

Notice that $\cos \frac{6\pi}7 = \cos \frac{8\pi}7$

$c$ is the negation of the product of roots by Vieta's formulas

$c = -\cos \frac{2\pi}7 \cos \frac{4\pi}7 \cos \frac{8\pi}7$

Multiply by $8 \sin{\frac{2\pi}{7}}$

$c \cdot 8 \sin{\frac{2\pi}{7}} = -8 \sin{\frac{2\pi}{7}} \cos \frac{2\pi}7 \cos \frac{4\pi}7 \cos \frac{8\pi}7$

Then use sine addition formula backwards:

$2 \sin \frac{2\pi}7 \cos \frac{2\pi}7 = \sin \frac{4\pi}7$

$c \cdot 8 \sin{\frac{2\pi}{7}} = -4 \sin \frac{4\pi}7 \cos \frac{4\pi}7 \cos \frac{8\pi}7$

$c \cdot 8 \sin{\frac{2\pi}{7}} = -2 \sin \frac{8\pi}7 \cos \frac{8\pi}7$

$c \cdot 8 \sin{\frac{2\pi}{7}} = -\sin \frac{16\pi}7$

$c \cdot 8 \sin{\frac{2\pi}{7}} = -\sin \frac{2\pi}7$

$c = -\frac{1}8$


Finally multiply $abc = \frac{1}2 * - \frac{1}2 * -\frac{1}8 = \frac{1}{32}$ or $\boxed{D) \frac{1}{32}}$.

~Tucker

Solution 2 (Approximation)

Letting the roots be $p$, $q$, and $r$, Vietas gives \[p + q + r = a\] \[pq + qr + pq = -b\] \[pqr = c\] We use the Taylor series for $\cos x$, \[\cos x = \sum_{k = 0}^{\infty} (-1)^k \frac{x^{2k}}{(2k)!}\] to approximate the roots. Taking the sum up to $k = 3$ yields a close approximation, so we have \[\cos\left(\frac{2\pi}{7}\right) \simeq 1-\frac{\left(\frac{2\pi}{7}\right)^{2}}{2}+\frac{\left(\frac{2\pi}{7}\right)^{4}}{24}-\frac{\left(\frac{2\pi}{7}\right)^{6}}{720} \simeq 0.623\] \[\cos\left(\frac{4\pi}{7}\right) \simeq 1-\frac{\left(\frac{4\pi}{7}\right)^{2}}{2}+\frac{\left(\frac{4\pi}{7}\right)^{4}}{24}-\frac{\left(\frac{4\pi}{7}\right)^{6}}{720} \simeq -0.225\] \[\cos\left(\frac{6\pi}{7}\right) \simeq 1-\frac{\left(\frac{6\pi}{7}\right)^{2}}{2}+\frac{\left(\frac{6\pi}{7}\right)^{4}}{24}-\frac{\left(\frac{6\pi}{7}\right)^{6}}{720} \simeq -0.964.\] Note that these approximations get worse as $x$ gets larger, but they will be fine for the purposes of this problem. We then have \[p + q + r = a \simeq -0.56\] \[pq + qr + pr = -b \simeq -0.524\] \[pqr = c \simeq 0.135\] We further approximate these values to $a \simeq -0.5$, $b \simeq 0.5$, and $c \simeq 0.125$ (mostly as this is an AMC problem and will likely use nice fractions). Thus, we have $abc \simeq \boxed{\textbf{(D) } \frac{1}{32}}$. ~ciceronii

Remark: In order to be more confident in your answer, you can go a few terms further in the Taylor series.

Solution 3 (Only Using Product to Sum Identity)

Note sum of roots of unity equal zero, sum of real parts equal zero, and $\text{Re} \omega^{m} = \text{Re} \omega^{-m},$ thus $\cos \frac{2 \pi}{7} + \cos \frac{4 \pi}{7} + \cos \frac{6 \pi}{7} = 1/2(0 - \cos 0) = -1/2$ which means $A = \frac{1}{2}.$

By product to sum, $\cos \frac{2 \pi}{7} \cos \frac{4 \pi}{7} + \cos \frac{2 \pi}{7} \cos \frac{6 \pi}{7} + \cos \frac{4 \pi}{7} \cos \frac{6 \pi}{7} = \frac{1}{2} (2 \cos \frac{2 \pi}{7} + \cos \frac{4 \pi}{7} + \cos \frac{6 \pi}{7} + \cos \frac{8 \pi}{7} + \cos \frac{10 \pi}{7})$ $= \frac{1}{2}(2 \cos \frac{2 \pi}{7} + 2 \cos \frac{4 \pi}{7} + 2 \cos \frac{6 \pi}{7}) = -1/2,$ so $B = - \frac{1}{2}.$

By product to sum, $\cos \frac{2 \pi}{7} \cos \frac{4 \pi}{7} \cos \frac{6 \pi}{7} = \frac{1}{2}(\cos \frac{2 \pi}{7} + \cos \frac{6 \pi}{7}) \cos \frac{6 \pi}{7} = \frac{1}{4}(\cos \frac{4 \pi}{7} +  \cos \frac{8 \pi}{7}) + \frac{1}{4}(1 + \cos \frac{12 \pi}{7})$ $= \frac{1}{4}(1 + \cos\frac{2\pi}{7} + \cos \frac{4\pi}{7} + \cos \frac{6\pi}{7}) = 1/8,$ so $C = -1/8.$

$ABC =\boxed{ \frac{1}{32}}.$

~ ccx09

Solution 4 (Complex Numbers)

Using geometric series, we can show that $\sum_{k=0}^{6}e^{\frac{2k\pi i}{7}}=0:$ \[\sum_{k=0}^{6}e^{\frac{2k\pi i}{7}}=1+e^{\frac{2\pi i}{7}}+e^{\frac{4\pi i}{7}}+\cdots+e^{\frac{12\pi i}{7}}=\frac{1-1}{1-e^{\frac{2\pi i}{7}}}=0.\]

Alternatively, note that the $7$th roots of unity are $z=e^{\frac{2k\pi i}{7}}$ for $i=0,1,2,\cdots,6,$ in which $z^7-1=0.$ By Vieta's Formulas, the sum of these seven roots is $0.$

It follows that the real parts of these complex numbers must sum to $0,$ so we get \begin{align*} \sum_{k=0}^{6}\cos\frac{2k\pi}{7}&=0 \\ \sum_{k=1}^{6}\cos\frac{2k\pi}{7}&=-1. \end{align*} Since $\cos\theta=\cos(2\pi-\theta)$ holds for all $\theta,$ we can rewrite this as \begin{align*} \cos\frac{2\pi}{7}+\cos\frac{4\pi}{7}+\cos\frac{6\pi}{7}+\underbrace{\cos\frac{8\pi}{7}}_{\cos\tfrac{6\pi}{7}}+\underbrace{\cos\frac{10\pi}{7}}_{\cos\tfrac{4\pi}{7}}+\underbrace{\cos\frac{12\pi}{7}}_{\cos\tfrac{2\pi}{7}}&=-1\\ 2\left(\cos\frac{2\pi}{7}+\cos\frac{4\pi}{7}+\cos\frac{6\pi}{7}\right)&=-1\\ \cos\frac{2\pi}{7}+\cos\frac{4\pi}{7}+\cos\frac{6\pi}{7}&=-\frac12. \end{align*}

Two solutions follow from here:

Solution 4.1 (Trigonometric Identities)

We know that $\theta=\frac{2\pi}{7},\frac{4\pi}{7},\frac{6\pi}{7}$ are roots of \[\cos\theta+\cos(2\theta)+\cos(3\theta)=-\frac12, \ \ \ \ \ (*)\] as they can be verified algebraically (by the identity $\cos\theta=\cos(-\theta)=\cos(2\pi-\theta)$ for all $\theta$) or geometrically (by the Remark section).

Let $x=\cos\theta.$ It follows that \begin{align*} \cos(2\theta)&=2\cos^2\theta-1 \\ &=2x^2-1, \\ \cos(3\theta)&=\cos(2\theta+\theta) \\ &=\cos(2\theta)\cos\theta-\sin(2\theta)\sin\theta \\ &=\cos(2\theta)\cos\theta-2\sin^2\theta\cos\theta \\ &=\cos(2\theta)\cos\theta-2\left(1-\cos^2\theta\right)\cos\theta \\ &=\left(2x^2-1\right)x-2\left(1-x^2\right)x \\ &=2x^3-x-2x+2x^3 \\ &=4x^3-3x. \end{align*} Rewriting $(*)$ in terms of $x,$ we have \begin{align*} x+\left(2x^2-1\right)+\left(4x^3-3x\right)&=-\frac12 \\ 4x^3+2x^2-2x-\frac12&=0 \\ x^3+\frac12 x^2 - \frac12 x - \frac18 &= 0, \end{align*} in which the roots are $x=\cos\frac{2\pi}{7},\cos\frac{4\pi}{7},\cos\frac{6\pi}{7}.$

Therefore, we obtain $(a,b,c)=\left(\frac12,-\frac12,-\frac18\right),$ from which $abc=\boxed{\textbf{(D) }\frac{1}{32}}.$

~MRENTHUSIASM (inspired by Peeyush Pandaya et al)

Solution 4.2 (Vieta's Formulas)

Let $z=e^{\frac{2\pi i}{7}}.$ Since $z$ is a $7$th root of unity, $z^7=1.$ Geometrically (shown in the Remark section), it follows that \begin{alignat*}{4} \cos{\frac{2\pi}{7}} &= \frac{z+z^6}{2} &&= \frac{z+z^{-1}}{2}, \\ \cos{\frac{4\pi}{7}} &= \frac{z^2+z^5}{2} &&= \frac{z^2+z^{-2}}{2}, \\ \cos{\frac{6\pi}{7}} &= \frac{z^3+z^4}{2} &&= \frac{z^3+z^{-3}}{2}. \end{alignat*} Recall that $\sum_{k=0}^{6}z^k=0$ (from which $\sum_{k=1}^{6}z^k=-1$), and let $(r,s,t)=\left(\cos{\frac{2\pi}{7}},\cos{\frac{4\pi}{7}},\cos{\frac{6\pi}{7}}\right).$ By Vieta's Formulas, the answer is \begin{align*} abc&=[-(r+s+t)](rs+st+tr)(-rst) \\ &=(r+s+t)(rs+st+tr)(rst) \\ &=\left(\frac{\sum_{k=1}^{6}z^k}{2}\right)\left(\frac{2\sum_{k=1}^{6}z^k}{4}\right)\left(\frac{1+\sum_{k=0}^{6}z^k}{8}\right) \\ &=\frac{1}{32}\left(\sum_{k=1}^{6}z^k\right)\left(\sum_{k=1}^{6}z^k\right)\left(1+\sum_{k=0}^{6}z^k\right) \\ &=\frac{1}{32}(-1)(-1)(1) \\ &=\boxed{\textbf{(D) }\frac{1}{32}}. \end{align*}

~MRENTHUSIASM (inspired by Peeyush Pandaya et al)

Remark (Geometric Representations)

Graph of the $7$th roots of unity in Desmos:

2021 AMC 12A Problem 22 Exact Values + LaTeX.png

Geometrically, it is clear that the imaginary parts of these complex numbers sum to $0.$

~MRENTHUSIASM

Video Solution by OmegaLearn (Euler's Identity + Vieta's )

https://youtu.be/Im_WTIK0tss

~ pi_is_3.14

See also

2021 AMC 12A (ProblemsAnswer KeyResources)
Preceded by
Problem 21
Followed by
Problem 23
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25
All AMC 12 Problems and Solutions

The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions. AMC logo.png

Invalid username
Login to AoPS